Integrating Training and Motivating to Improve Sustainable Performance in a Cross-Cultural Context - Yang, Huan; Gustomo, Aurik (Journal Integration of Management Studies, 2025)
It is estimated that more than half of those Chinese MNEs(Muti-national enterprise) operating in Indonesia have been continuing lose money in recent 3 years due to different culture, language and business practice, etc. The once effective leadership style in China becomes ineffective in Indonesia. How to operate sustainably in Indonesia is rising as one of the biggest challenges faced by Chinese MNEs in Indonesia. This is the first time to study all these variables with cultural adaptation, leadership style, workplace and work-life balance as independent variables and employees’ satisfaction, performance and commitment as dependent variables from both theoretical and practical ways. With the help of mathematical multiple regression methods, there are several notable findings. 1. To increase the investment in cultural adaptation, leadership style, work-life balance and workplace will improve the employee satisfaction, employee performance and employee commitment. 2. Cultural adaptation and work place affect the employee satisfaction and performance the most. The leadership style impact the employee commitment the most. By introducing and applying the integrating training & motivation(ITM) solution, Chinese MNEs will improve the performance sustainably. Keywords: cultural adaptation, leadership, employee satisfaction, cross-culture